2018
DOI: 10.1073/pnas.1806077115
|View full text |Cite
|
Sign up to set email alerts
|

Specific oxylipins enhance vertebrate hematopoiesis via the receptor GPR132

Abstract: Epoxyeicosatrienoic acids (EETs) are lipid-derived signaling molecules with cardioprotective and vasodilatory actions. We recently showed that 11,12-EET enhances hematopoietic induction and engraftment in mice and zebrafish. EETs are known to signal via G protein-coupled receptors, with evidence supporting the existence of a specific high-affinity receptor. Identification of a hematopoietic-specific EET receptor would enable genetic interrogation of EET signaling pathways, and perhaps clinical use of this mole… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 65 publications
2
27
0
Order By: Relevance
“…release and reesterification) of free oxylipins (Otoki et al, 2020). Free oxylipins are more bioactive than esterified oxylipins (Lahvic et al, 2018;Obinata et al, 2005), consistent with studies showing that they act as signaling molecules (Hennebelle et al, 2019). Thus, understanding their localization and proportional distribution relative to esterified pools in human milk would inform on how milk serves as a signaling system in infants.…”
Section: Introductionsupporting
confidence: 70%
“…release and reesterification) of free oxylipins (Otoki et al, 2020). Free oxylipins are more bioactive than esterified oxylipins (Lahvic et al, 2018;Obinata et al, 2005), consistent with studies showing that they act as signaling molecules (Hennebelle et al, 2019). Thus, understanding their localization and proportional distribution relative to esterified pools in human milk would inform on how milk serves as a signaling system in infants.…”
Section: Introductionsupporting
confidence: 70%
“…This is because receptors for both compounds within neuron‐glia are not known. Recent studies have characterized GPR132 (also known as G2A) as a receptor for various FFAs and oxylipins, but it is not known to be selective for LA or 13‐HODE (Obinata et al ; Lahvic et al ). Identifying the receptor for LA and 13‐HODE in brain could help determine the molecular pathways and mechanisms underlying their sex‐specific effects on neuronal morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the linoleic acid metabolites 9- and 13-HODE were increased at the injured nerves in wild-type mice 7 days after the SNI surgery ( Figure 1 C,E), both of which are endogenous agonists of G2A ( Figure 1 B). Moreover, we could detect a strong increase of the lipid 12,13-epoxyoctadecenoic acid (EpOME) in the injured ipsilateral site of the nerve, which was recently identified as weak G2A agonist ( Figure 1 G) [ 43 ]. In contrast, G2A-deficient mice did not show any difference between the treated (ipsilateral) and untreated sites (contralateral) regarding the different lipid concentrations ( Figure 1 D,F,H,J).…”
Section: Resultsmentioning
confidence: 99%